Organizational change in the history of Rimini hotels - Bagnaresi, Davide; Barbini, Francesco Maria; Battilani, Patrizia (Piccola Impresa / Small Business, 2017)
What are the most relevant organizational changes that are taking place in hotels? This longitudinal research on the Rimini case investigates the issues pertaining to the trajectories of development of family hotels and their organizational change. In order to understand the actual dynamics of entrepreneurship development and the organizational choices implemented by the hospitality industry in Rimini, an ambitious research project is being conducted. This paper presents the preliminary results emerging from a quantitative survey and from qualitative interviews, in order to depict the evolutionary paths, the dynamics of generational shift and organizational changes that have been taking place in Rimini hotels for more than sixty years. The result is a unique picture, rich in details and evidences, of one of the most important cases of hospitality management in the world.